Desalination (IntechOpen, 2020)
Undoubtedly, drinking water of an acceptable quality has become a scarce commodity. Water shortage is becoming a major concern all around the world due to limited freshwater resources as well as the high cost of freshwater transportation from freshwater-rich areas to arid areas. As a result, solutions such as water recycling and desalination of saline or brackish water are being introduced and emerging worldwide as alternative ways of supplying water. Desalination of seawater is known to be one of mankind’s earliest forms of water treatment, and it has become one of the most sustainable alternative solutions to provide freshwater for many communities and industrial sectors. This book aims to cover the challenges and opportunities in desalination processes.